2005
DOI: 10.1207/s1532785xmep0702_4
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Image Quality: The Case of High-Definition Television

Abstract: Previous research has demonstrated that form variables can increase television viewers' sense of presence. The current broadcasting of high-definition television (HDTV) programming makes testing this relation between form and presence possible in a new context, image quality. In this experiment, television viewers watched either HDTV or standard-definition television images and then rated their viewing experience on a pencil-and-paper questionnaire. The results demonstrate that HDTV provided viewers with a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 11 publications
5
102
1
2
Order By: Relevance
“…They also suggested that presence appears to be part of the mental state in which persuasion via mediated environments such as the television can be significantly improved. More recently, it was reported that high-definition television (HDTV) viewers experience higher involvement with the television content while they perceive the greater amount of presence [5].…”
Section: Presence and High-definition Video Viewingmentioning
confidence: 99%
See 3 more Smart Citations
“…They also suggested that presence appears to be part of the mental state in which persuasion via mediated environments such as the television can be significantly improved. More recently, it was reported that high-definition television (HDTV) viewers experience higher involvement with the television content while they perceive the greater amount of presence [5].…”
Section: Presence and High-definition Video Viewingmentioning
confidence: 99%
“…With the recent wide availability of HDTV, several studies have been conducted to test the effect of image quality. For example, Bracken [5], [20] reported that enhanced image quality in television can generate a strong sense of presence. Bracken [5], in her experiment investigating the level of presence on HDTV, found that the improved image quality on HDTV increased the higher level of presence than that on SDTV over the same content.…”
Section: The Influence Of Video Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although work has been undertaken to assess perceived/subjective media quality in terms of frame rate [1][3], resolution [2], and on specific devices [5] [6],to the best of our knowledge, the question of how subjective media quality is impacted when the same content is viewed across different devices has not been explored.…”
Section: Introductionmentioning
confidence: 99%